Effect of Tumor Necrosis Factor Family Member LIGHT (TNFSF14) on the Activation of Basophils and Eosinophils Interacting with Bronchial Epithelial Cells - Huai Na Qiu; Chun Kwok Wong; Jie Dong; Christopher Wai-Kei Lam; Zhe Cai (Mediators of Inflammation)
Allergic asthma can cause airway structural remodeling, involving the accumulation of extracellular matrix and thickening of smooth muscle. Tumor necrosis factor (TNF) family ligand LIGHT (TNFSF14) is a cytokine that binds herpesvirus entry mediator (HVEM)/TNFRSF14 and lymphotoxin β receptor (LTβR). LIGHT induces asthmatic cytokine IL-13 and fibrogenic cytokine transforming growth factor-β release from allergic asthma-related eosinophils expressing HVEM and alveolar macrophages expressing LTβR, respectively, thereby playing crucial roles in asthmatic airway remodeling. In this study, we investigated the effects of LIGHT on the coculture of human basophils/eosinophils and bronchial epithelial BEAS-2B cells. The expression of adhesion molecules, cytokines/chemokines, and matrix metalloproteinases (MMP) was measured by flow cytometry, multiplex, assay or ELISA. Results showed that LIGHT could significantly promote intercellular adhesion, cell surface expression of intercellular adhesion molecule-1, release of airway remodeling-related IL-6, CXCL8, and MMP-9 from BEAS-2B cells upon interaction with basophils/eosinophils, probably via the intercellular interaction, cell surface receptors HVEM and LTβR on BEAS-2B cells, and extracellular signal-regulated kinase, p38 mitogen activated protein kinase, and NF-κB signaling pathways. The above results, therefore, enhance our understanding of the immunopathological roles of LIGHT in allergic asthma and shed light on the potential therapeutic targets for airway remodeling.